THE PLANETARY HOST RED GIANT HD47536 - CHEMICAL COMPOSITION AND SIGNS OF ACCRETION - Yushchenko, A. V.; Rittipruk, P.; Yushchenko, V. A.; Kang, Y.-W. (Одеські астрономічні публікації, 2013)
The spectra of HD47536 with resolving power R=30,000 and signal to noise ratio near 100 was obtained at 1.5 meter SMART telescope of CTIO, Chile.The analysis of chemical composition allowed to ﬁnd the abundances of 33 chemical elements including thorium. The star belongs to halo or intermediate population, it’s metallicity is[Fe/H]=-0.580.11, the r-and s-processes elements are over abundant with respect to iron.The overabundance of thorium with respect to ironis+0.72dex. The abundance pattern exhibits the clear signs of accretion. The star is a host of two planets, that is why it can be the result of the accretion in planetary system or the accretion of interstellar gas. The signs of accretion are clearly detected and prevent the determination of stellar age.